2009
DOI: 10.1542/peds.2009-1542i
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Universal Influenza Vaccination of Children in Pediatric Practices

Abstract: Context-Although all children 6 months to 18 years are now recommended to receive influenza vaccine, the total direct and indirect costs for pediatric practices of delivering childhood influenza vaccination are unknown.Objective-To estimate nationally-representative pediatric practices' costs of providing influenza vaccination during the 2006-2007 season, and to simulate the costs pediatric practices might incur when implementing universal influenza vaccination for US children 6 months to 18 years.Design and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 21 publications
4
34
1
Order By: Relevance
“…Several recent studies of private pediatricians documented the potential for financial losses, from both vaccine purchase and vaccine administration, associated with providing vaccines to children and adolescents. [41][42][43][44] Concerns about reimbursement for vaccine purchase may be increasing as more-expensive vaccines are recommended for routine use. Two recent studies showed significant variation in both the prices private pediatric practices pay for identical vaccines and the insurance reimbursements they receive.…”
Section: Pressure On Private-sector Providersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies of private pediatricians documented the potential for financial losses, from both vaccine purchase and vaccine administration, associated with providing vaccines to children and adolescents. [41][42][43][44] Concerns about reimbursement for vaccine purchase may be increasing as more-expensive vaccines are recommended for routine use. Two recent studies showed significant variation in both the prices private pediatric practices pay for identical vaccines and the insurance reimbursements they receive.…”
Section: Pressure On Private-sector Providersmentioning
confidence: 99%
“…42 In general, private insurers reimburse more for vaccine administration than Medicaid reimburses for VFC vaccine administration. [42][43][44] However, even private insurance reimbursements vary widely and do not always cover a provider's cost to administer vaccines. 42,43 Providing vaccination services to both privately and publicly insured children and adolescents may be financially unsustainable for some practices, particularly if they serve larger proportions of VFCeligible patients.…”
Section: Pressure On Private-sector Providersmentioning
confidence: 99%
“…Along with capacity issues, primary care practices also bear financial risks related to vaccine purchase and may face inadequate reimbursement rates for administering vaccination, which might discourage some practices from expanding their vaccine provision [7, 9, 10]. For instance, practices are often fearful of ordering too many vaccine doses that they may not use and would have to discard, leading to a financial loss at the end of an influenza season [7, 11].…”
Section: Introductionmentioning
confidence: 99%
“…13,15,28,39 Challenges to implementing universal influenza vaccination exclusively by primary care physicians have driven expanded use of school-located influenza vaccination as a viable delivery method. 20,21,28 Future school-located influenza vaccination programs might encounter less physician resistance if this delivery method continues to expand toward widespread use.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Implementing expanded vaccination recommendations has challenged primary care physicians, who administer the majority of vaccines to children in the United States. 2,[12][13][14][15] Sole reliance on primary care physicians to provide these vaccines may not achieve high coverage rates among children and adolescents. 5,13,14 Supplementary venues to deliver vaccines (eg, schools, emergency departments,pharmacies)havebeen proposed as a means of increasing vaccination rates while reducing the burden on primary care physicians.…”
mentioning
confidence: 99%